Islamic Counseling as a Pedagogical Strategy for Adolescent Character Development in Globalized Education - Harahap, Siti Rahma; Daulay, Ainun Adilah; Padilah, Nurul; Afriani , Armina; Soraya , Aulia; Aisyah, Rahmi Aisyah; Lubis , Fatwa Aulia; Efendi , Amir Hamzah (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
This research discusses Islamic counseling guidelines as an effort to build adolescent character amidst the challenges of globalization, with a focus on its implementation at SMK N 1 Panyabungan. Globalization has a major influence on the values and behavior of teenagers, which often conflict with Islamic values. Islamic counseling exists as a solution to help teenagers develop positive character based on religious values. This approach involves spiritual methods, moral education, and the formation of self-awareness through Islamic teachings, such as prayer, dhikr, and understanding the Koran. This research uses a qualitative approach by collecting data through interviews, observation and literature study. The results of the research show that Islamic counseling is effective in increasing students' spiritual and moral awareness, so that they can form the character of teenagers who are tough, independent and have integrity during globalization. This article concludes that Islamic counseling guidelines can be a strategic tool in character education for adolescents in the school environment.